Isolated Peripheral Tuberculous Lymphadenitis: Insights into Diagnostic Delays and Clinical Challenges - Gürcüoğlu, Emel (The European Research Journal, 2026)
Objectives: Peripheral tuberculous lymphadenitis (TB-LAP) is the most common form of extrapulmonary tuberculosis (EPTB) and remains diagnostically challenging due to its low bacillary burden. This study aimed to evaluate diagnostic pathways, microbiological confirmation rates, and treatment outcomes in adult TB-LAP cases. Methods: We retrospectively analyzed 30 adult patients diagnosed with TB- LAP at a tertiary care center between 2021 and 2025. Inclusion criteria were isolated peripheral lymphadenopathy with compatible histopathology, supported by culture, PCR, or clinical-radiological findings. Data regarding diagnostic delay, referral pathways, microbiological yield, and treatment outcomes were collected. Results: Among 158 peripheral lymphadenopathy cases, 52 were diagnosed as TB-LAP, and 30 with complete follow-up data were included in the final analysis. The mean age was 39.2 years, and 83.3% were female. Culture positivity was 28.6%, Polymerase Chain Reaction (PCR) 42.9%, and acid-fast bacilli were detected in only one patient. Overall microbiological confirmation rate was 23.3%. Treatment was successfully completed in most cases, with treatment-related complication rate of 6.7%. Diagnostic delay ≥2 months was observed in 56.7% of patients. Early referral to the infectious diseases clinic significantly reduced diagnostic delay (<2 months in 72.7% vs. 15.4% in internal medicine; P=0.017). Histopathology most frequently showed granulomatous inflammation, while caseating necrotizing inflammation (23.3%) was the strongest supportive finding. Conclusions: In this 30-case series of isolated peripheral TB-LAP, histopathology - supported by PCR when available - provided the most reliable diagnostic contribution, while culture remained limited in keeping with the paucibacillary nature of the disease. The findings highlight the need for more sensitive molecular tools, yet indicate that, for now, timely tissue sampling and careful clinical–pathological interpretation remain the most dependable approach in routine practice.